Carbon-carbon coupling reactions of but-2-yne on a triruthenium framework: synthesis and molecular structure of Ru-3(CO)(7)[NS(O)MePh] (HCMeCMeCMeCMeCO) and Ru-3(CO)(8)(CMeCMeCMeCMe) - Ferrand, Vincent; Neels, Antonia; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 1999)
The cluster HRu3(CO)(9)[NS(O)MePh] (1) reacts with two equivalents of MeC=CMe in tetrahydrofuran at 60 degrees C to give the dienonyl derivative Ru-3(CO)(7)[NS(O)MePh] (HCMeCMeCMeCMeCO) (2), along with an isomer mixture of Ru-3(CO)(8)[NS(O)MePh] (HCMeCMe) (3). At 100 degrees C, the same reaction gives rise to the formation of the diendiyl cluster Ru-3(CO)(8)(CMeCMeCMeCMe) (4). The single-crystal structure analyses reveal for 2 a closed Ru-3 skeleton and for 4 an open Ru, framework. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: alkyne complexes; dimerisation; cluster complexes; ruthenium complexes; crystal structures; CLUSTERS; ALKYNES